2009
DOI: 10.1055/s-0029-1186144
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Diterpenes Isolated from the Brazilian Brown AlgaeDictyota pfaffiiandDictyota menstrualisagainst the Herpes Simplex Type-1 Replicative Cycle

Abstract: We describe in this paper that the diterpenes 8,10,18-trihydroxy-2,6-dolabelladiene ( 1) and (6 R)-6-hydroxydichotoma-4,14-diene-1,17-dial ( 2), isolated from the marine algae DICTYOTA PFAFFII and D. MENSTRUALIS, respectively, inhibited HSV-1 infection in Vero cells. We initially observed that compounds 1 and 2 inhibited HSV-1 replication in a dose-dependent manner, resulting in EC (50) values of 5.10 and 5.90 microM, respectively, for a multiplicity of infection (MOI) of 5. Moreover, the concentration require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…The screening of natural products derived vitro effects of diterpenes with encouraging results for antiviral activity (Abrantes et al, 2010;Khan et al, 2005;Siamopoulou et al, 2004;Suzuki et al, 2002). Several studies with natural products demonstrate their potential role in inhibiting certain diseases, as well as their good performance during the active stage of viral replication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The screening of natural products derived vitro effects of diterpenes with encouraging results for antiviral activity (Abrantes et al, 2010;Khan et al, 2005;Siamopoulou et al, 2004;Suzuki et al, 2002). Several studies with natural products demonstrate their potential role in inhibiting certain diseases, as well as their good performance during the active stage of viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…The diterpene, at over 99% purity, was diluted in 100% dimethyl sulfoxide (DMSOMerck) and stored at -20 °C. The resulting DMSO concentrations during the assays were below 0.1%, a level that is not significantly cytotoxic (Abrantes et al, 2010).…”
Section: Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…These molecules are the products of secondary metabolism and display pharmacological properties (Mayer et al, 2007;Cirne-Santos et al, 2008;Abrantes et al, 2010) as well as ecological functions (Bianco et al, 2009). A previous study demonstrated that L. muta venom displayed phospholipase A 2 (indirect hemolytic activity), hemorrhagic, clotting and proteolytic activities (Fuly et al, 1993).…”
Section: Resultsmentioning
confidence: 99%